Aortic root reconstruction through valve-sparing operation: critical analysis of 11 years of follow-up - Dias,Ricardo Ribeiro (2010)
INTRODUCTION: The composite mechanical valve conduit replacement is the standardized operation for aneurysms of the aortic root. The objective of this study is to evaluate the long-term surgical results of aortic valve-preserving procedures to the root reconstruction. METHODS: From 1996 to 2008, 54 consecutive patients underwent two different techniques of valve-sparing aortic root operation (40 Yacoub operations and 14 David operations). Mean age was 48 ± 14 years (range 17 to 74). 36 patients (66.7%) were male and 16 (29.6%) experienced Marfan's syndrome. The mean Euroscore was 4 ± 1.25. The mean follow up time was 4.1 years (from 49 days to 10.9 years). Clinical and echocardiographic parameters were analysed. T-Student paired test, the McNemar Non Parametric test and the Kaplan-Meyer Outcome Curves have been used. RESULTS: The hospital mortality was 5.6% and the average hospitalization time was 9±4 days. One non related late death (2%) was reported. The actuarial survival and freedom from reoperation were respectively 94.4% and 96% within 11 years of follow-up. There were benefits in reduction of functional class (P=0.002; 78% CF I), in reduction of aortic regurgitation (P<0.001; 78% with or without discrete reflux), in reduction of systolic and diastolic diameters, end-sytolic and end-diastolic volumes of left ventricle (respectively P=0.004; P<0.0001; P=0.036 and P<0.001). Two (3.9%) patients required aortic valve replacement due to severe aortic regurgitation during this same period. No thromboembolic, endocarditis or bleeding events were reported during the follow-up. CONCLUSION: The valve-sparing operation for aortic root aneurysms is an effective alternative to the use of a mechanical valve conduit replacement.